RASIONALITAS TINDAKAN SOSIAL NGAYAH MUDA-MUDI DI PURA AGUNG WIRA DHARMA SAMUDRA CILANDAK JAKARTA SELATAN - Jaya Negara, Ida Bagus Ngurah; Bagus Suka Arjawa, I Gusti Putu; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
daldaABSTRACTdana This study takes three formulations of the problem; how are the forms of ngayah performed by young people, what are the inhibiting factors for young people to get rich, and how is the meaning of rationality of ngayah activities in temples for young people carried out at Agung Wira Dharma Samudera Cilandak Temple in South Jakarta. The theory in this study came from a sociologist, Max Weber. The results showed that the form of ngayah was cleaning the temple area, preparing religious ceremonial activities. Economic activities in the form of cooperatives to help maintain the temples and temple members who do not have permanent jobs as instrumental rationality and values. The inhibiting factor caused by time constraints, there is no support from some parents and it is difficult to get permission from agencies such as offices and schools. Keywords; Ngayah, Young, Rationality, Social Action.